Priorities in Religious Education A model for the 1990s and Beyond - Watson, Brenda (Washington D.C The Falmer Press, 2005)
A collection of articles which look at the future development of religious education in the light of the 1988 Education Reform Act and at how religious education should now develop in schools. It contains practical guidance for meetings and workshops and
this edition published in Taylor & Francis e-Library, 2005
Keywords: Religious education. Schools -- Curriculum -- Religion Great Britain